Study on Heavy Metal Removal Rates According to Lithium Content in Post-Use Induction Top Plate Comminuted Powder - Wang, Jei-Pil; Erdenebold, Urtnasan; Lim, Hankwon (International Journal of Membrane Science and Technology, 2023)
This study investigated the liquid-phase adsorption reactions of heavy metal ions (Pb, Cd, Cr6+, Hg) in wastewater using post-use Li2O-Al2O3-SiO2 crystalline glass derived from induction top plate materials. The heavy metal ion adsorption characteristics were compared using samples before and after the Li removal process in LAS sample. The amount of zeolite used as an adsorbent, adsorption time, concentration of heavy metal elements, and pH were examined for their effects on adsorption capacity. Lithium-removed zeolite demonstrated an average improvement of 30% in heavy metal adsorption ability compared to conventional LAS zeolite. As the amount of zeolite added increased, the heavy metal adsorption removal rate also increased. Adsorption reaction time significantly influenced adsorption characteristics, with a notable improvement in the removal rate of Cd. Additionally, the adsorption removal rate of Cd increased with increasing pH, while that of Pb and Cr6+ decreased. The adsorption characteristics of Hg were not significantly affected by pH.